2001
DOI: 10.3127/ajis.v9i1.219
|View full text |Cite
|
Sign up to set email alerts
|

Impediments to Inter-Firm Transfer of Best Practice in an Enterprise Systems Context

Abstract: A survey of major issues with Enterprise Systems was administered within the State Government of Queensland, Australia and a subset of these issues mapped against Szulanski's model of inter-firm best practice transfer stickiness (Szulanski, G. 1996. Exploring internal stickiness: Impediments to the transfer of best practice within the firm. Strategic Management Journal, 17(Special Issue), 27-43). The paper discusses impediments to knowledge transfer within this context, presents findings from the a posteriori … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Xu and Ma (2008, p. 529) defined causal ambiguity as -the lack of understanding of the logical linkage between action and outcomes, inputs and outputs, and causes and effects‖. Timbrell et al (2001) examined the characteristics of knowledge in IS outsourcing projects in Australia and found that knowledge with high causal ambiguity is more challenging and much harder to transfer than less ambiguous knowledge. It can be concluded, therefore, that the greater the ambiguity of the causes and effects of the knowledge, the more difficult is to identify the related knowledge elements and subsequently the chances of transferring the knowledge are limited.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xu and Ma (2008, p. 529) defined causal ambiguity as -the lack of understanding of the logical linkage between action and outcomes, inputs and outputs, and causes and effects‖. Timbrell et al (2001) examined the characteristics of knowledge in IS outsourcing projects in Australia and found that knowledge with high causal ambiguity is more challenging and much harder to transfer than less ambiguous knowledge. It can be concluded, therefore, that the greater the ambiguity of the causes and effects of the knowledge, the more difficult is to identify the related knowledge elements and subsequently the chances of transferring the knowledge are limited.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Joshi et al (2007, p. 326) defined source credibility as -the extent to which a recipient perceive a source to be trustworthy and reputable‖. Trust is the believe that the source' word is reliable and that it will fulfil its obligation as stipulated in the agreement (Timbrell et al, 2001). Lee et al (2008) investigated the impact of trust on IS outsourcing success and found that mutual trust facilitate knowledge sharing between vendors and clients.…”
Section: Source-relatedmentioning
confidence: 99%
“…For example, in their study of enterprise system use by the State Government of Queensland, Australia, Timbrell et al (2001) find empirical evidences to support the significant effect of the characteristics of knowledge, the source and the recipient, arduous relationship between the source and the recipient, and barren organizational context on the transfer of best practices. Similarly, Ko et al (2005) examine the knowledge transfer from consultants to client organizations in enterprise system implementations, and conclude the significant performance impact of the set of factors, including motivation of source and recipient, their encoding and decoding competence, shared understanding, and the arduous relationship.…”
Section: Knowledge Transfer In Organizationsmentioning
confidence: 95%
“…Consulting companies were one of three groups, depending on performance. [11,27] The characteristics of recipient Communication decoding competence [11] Acquisition willingness [14,30,34] Absorptive capacity [14,18,30,32,35] 4.2. Data collection procedure 4.2.1.…”
Section: Measurement Of Control Variablesmentioning
confidence: 99%
“…impediments to knowledge transfer); it had a negative effect on knowledge transfer. Timbrell et al [32] explored the stickiness origins of ES best practice transfer. In their study, causal ambiguity did not rank within the top 4 factors in any transfer phase.…”
Section: Hypothesesmentioning
confidence: 99%